1D Mixed‐Stack Cocrystals Based on Perylene Diimide toward Ambipolar Charge Transport. Issue 20 (6th April 2021) - Yu, Panpan; Li, Yang; Zhao, Huijuan; Zhu, Lingyun; Wang, Yongshuai; Xu, Wei; Zhen, Yonggang; Wang, Xinran; Dong, Huanli; Zhu, Daoben; Hu, Wenping
Abstract: There is very limited repertoire of organic ambipolar semiconductors to date. Electron donor–acceptor alternative stacking is a unique and important binary motif for 1D mixed‐stack cocrystals, opening up possibilities for the development of organic ambipolar semiconductors. Herein, four 1D mixed‐stack cocrystals using N, N ′‐bis(perfluorobutyl)‐1, 7‐dicyanoperylene‐3, 4:9, 10‐bis(dicarboximide) (PDICNF) as the acceptor and anthracene, pyrene, perylene, and meso ‐diphenyl tetrathia[22]annulene[2, 1, 2, 1] (DPTTA) as the donors are achieved in a stoichiometric ratio (D:A = 1:1) through solution or vapor processed methods. Their packing structures, energy levels, charge transfer interactions, coassembling behaviors, and molecular orientations are systematically investigated by single‐crystal X‐ray analysis, absorption spectra, fluorescence quenching, Job's curve plot, and polarized photoluminescence measurements with the help of theoretical calculations. The donor–acceptor alternative stacking direction coincides with the long axis for all the four cocrystals. The field‐effect transistors based on Pyrene‐PDICNF show the electron mobility up to 0.19 cm 2 V −1 s −1, which is the highest value among perylene diimide‐based cocrystals. Moreover, DPTTA‐PDICNF cocrystals possess well‐balanced electron and hole mobility with 1.7 × 10 −2 and 2.0 × 10 −2 cm 2 V −1 s −1 respectively due to both hole and electron strong superexchange interactions, shedding light on the design of 1D mixed‐stack cocrystals with excellent ambipolar transport behaviors. Abstract : Four 1D mixed‐stack cocrystals using perylene diimide as the acceptor are achieved with tunable charge transporting behaviors from n‐type to ambipolarity. The in‐depth investigation of the relationship among molecular structures, packing arrangements, and charge transport properties can shed light on the design of 1D mixed‐stack cocrystals with excellent ambipolar transport behaviors.